2015
DOI: 10.1001/jamaoncol.2015.2590
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Acute Toxic Effects of Breast Radiotherapy by Fractionation Schedule

Abstract: Hypofractionation not only improves convenience but also may reduce acute pain, fatigue, and the extent to which patients are bothered by dermatitis in patients with breast cancer undergoing whole-breast radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
65
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(75 citation statements)
references
References 34 publications
8
65
0
2
Order By: Relevance
“…The main motivation for developing protracted radiotherapy regimens was the benefit to patients and health services in terms of convenience and cost. Recent breast cancer studies suggested that HF is also associated with a significantly lower acute skin reaction rate compared with CF [7, 24, 25]. Our study revealed another advantage of HF over CF: a significantly better patient compliance with the prescribed radiotherapy schedule.…”
Section: Discussionsupporting
confidence: 49%
“…The main motivation for developing protracted radiotherapy regimens was the benefit to patients and health services in terms of convenience and cost. Recent breast cancer studies suggested that HF is also associated with a significantly lower acute skin reaction rate compared with CF [7, 24, 25]. Our study revealed another advantage of HF over CF: a significantly better patient compliance with the prescribed radiotherapy schedule.…”
Section: Discussionsupporting
confidence: 49%
“…The two UK trials also showed that HF-WBI has similar or less late toxicities to normal breast tissues, compared to conventional radiotherapy [6]. Recently, two studies conducted in the US demonstrated that HF-WBI had significantly lower rates of early toxicities than conventional radiotherapy [18, 19], and a 2-year follow-up of the clinical trial in the US showed that patient-reported quality of life and physician-assessed cosmetic outcomes were similar between HF-WBI and CF-WBI arms [20]. Therefore, there should be no fear for toxicities to adopt HF-WBI.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the theoretically higher risk of late side effects, hypofractionation may provide benefits regarding the treatment-related quality of life and acute toxicity [10]. In study by Jagsi et al [11], patients who underwent hypofractionated whole breast radiotherapy presented with less acute pain, fatigue and dermatitis than patients who had received conventionally fractionated treatment.…”
Section: Introductionmentioning
confidence: 99%